THE ROLE OF TEACHERS IN IMPROVING STUDENT DISCIPLINE AT SMA 1 TENGGARONG SEBERANG - Setiawan, Hendri; Marwiah, Marwiah; Bahzar, M (Unmul Civic Education Journal, 2021)
The purpose of the study was to describe the role of teachers in improving student discipline at SMAN 1 Tenggarong Seberang. This type of research is descriptive qualitative by using the research focus, namely the role of teachers in improving student discipline at SMAN 1 Tenggarong Seberang, obstacles faced in improving student discipline at SMAN 1 Tenggarong Seberang, and efforts made by teachers in overcoming obstacles in improving the discipline of students of SMAN 1 Tenggarong Seberang. Data collection techniques include interviews, observations, and documentation. Data analysis techniques include: collection, data reduction, data display, and drawing conclusions. The results of the study concluded that the role of teachers in improving student discipline is very important, where teachers as mottovators and facilitators to direct, apply, and instill discipline itself, because it is in line with the school's goal of programming itself into every level of education, so that every student understands and has a disciplined attitude as a student. Attitudes such as punctual discipline, appearance discipline, learning discipline, and environmental discipline the role of the teacher is not only as teaching, but more than that the figure of the teacher sets an example and makes himself a role model figure for students.